Export Market Orientation Small and Medium Size Business as A Case Study of Erbil Northern Iraq - Hussein, Jutyar Abdulrahman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The objective of this research is to determine if there is significant relationship between export market orientation (EMO) and export performance of small and medium enterprises (SMEs) in Erbil northern Iraq. Quantitative survey method was employed and data were collected from 40 exporting SMEs registered with the Federation of Erbil Manufacturers. Regression analysis, one sample t-test and many other statistics analysis was used to test the relationship between export performance as a dependent variable and export market orientation such as “ intelligence generation , intelligence_ dissemination , responsiveness coordinating _mechanism” an independent variable. The finding emphasizes the importance of developing EMO among the owner/managers of SMEs for their success. Those owner/managers that adopt EMO activities in their firms would gain in terms of competitive advantage over their rivals and reap higher export performance... The study limitations and implications are discussed as well as a number of directions for further research.

ÖZ: Bu araştırmanın amacı Erbil doğu Irak‟taki Dış Pazar Odaklı (DPO) ile küçük ve orta boy işletmelerin (KOBİ) piyasa performansı arasında kayda değer bir ilişkinin bulunup bulunmadığını ortaya koymaktır. Kantitatif anket yöntemi kullanılarak Erbil İmalatçılar Federasyonu işbirliğiyle ihracat yapan 40 küçük ve orta işletmeden bilgiler elde edilmiştir. İhracat performansı bağımlı değişkeni ile “akıl jenerasyonu, akıl yayılımı, çözüm koordinasyon mekanizması” etkenleri içeren dış pazar odak bağımsız değişkeni arasındaki ilişkiyi belirlemek için regresyon analizi, tek grup t-testi ve daha birçok istatistik analizlerden faydalanılmıştır. Yapılan tespitler, küçük ve orta işletme sahiplerinin başarıya ulaşabilmeleri için işletmelerinde Dış Pazar Odaklı politika geliştirmeleri gerekliliğinin önemini vurgulamaktadır. İşletmelerinde DPO politikasına sahip olan işletmeciler, rakipleri karşısında rekabet üstünlüğüne sahip olup daha yüksek ihracat performansı elde etmektedir.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Financial Enterprises--Business--Erbil (Iraq); Export market orientation; Small medium business; Business performance; Erbil Northern Iraq